Edible Snail Production in Europe - Anna Rygało-Galewska; Klara Zglińska; Tomasz Niemiec (Animals, 2022)
The human population is growing; food production is becoming insufficient, and the growing awareness of the negative impact of traditional animal husbandry on the environment means that the search for alternative methods of providing animal protein is continuously underway. The breeding of edible snails seems to be a promising option. The most popular species of edible snails in Europe include the brown garden snail Cornu aspersum (Müller, 1774) (previously divided into two subspecies: Cornu aspersum aspersum (Müller, 1774) and Cornu aspersum maxima (Taylor, 1883)), as well as the Roman Snail—Helix pomatia Linnaeus, 1758. These animals are highly productive, require relatively little space, are easy to breed and their maintenance does not require large financial outlays. This review focuses on the prospects of food snail farming in Europe. It discusses the living conditions, the nutritional value of the snails’ meat, and the way of feeding the animals, paying particular attention to issues still not scientifically resolved, such as the need for micro and macro elements, as well as fat and carbohydrates.